All Days 2015
DOI: 10.4043/25948-ms
|View full text |Cite
|
Sign up to set email alerts
|

Vision 2020- Delivering Great Process Safety Globally

Abstract: Vision 20/20, developed by the Center for Chemical Process Safety (CCPS), looks into the not-too-distant future to describe how great process safety is delivered when it is collectively and fervently supported by industry, regulators, academia, and the community worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It has been shared within CCPS member companies, as well as with the Institution of Chemical Engineers (IChemE), 2 the American Institute of Chemical Engineers (AIChE), 3 and the Offshore Technology Conference. 4 In 2015, the US Environmental Protection Agency (EPA) indicated support for the stakeholder collaboration called for by Vision 20/20 and indicated that the EPA's report "Actions to Improve Chemical Facility Safety and Security-A Shared Commitment" was very much in alignment with this concept. 5 One EPA blog entry stated "There is a tremendous nexus between Vision 20/20 and the report for the president.…”
Section: Impact Of Vision 20/20mentioning
confidence: 99%
“…It has been shared within CCPS member companies, as well as with the Institution of Chemical Engineers (IChemE), 2 the American Institute of Chemical Engineers (AIChE), 3 and the Offshore Technology Conference. 4 In 2015, the US Environmental Protection Agency (EPA) indicated support for the stakeholder collaboration called for by Vision 20/20 and indicated that the EPA's report "Actions to Improve Chemical Facility Safety and Security-A Shared Commitment" was very much in alignment with this concept. 5 One EPA blog entry stated "There is a tremendous nexus between Vision 20/20 and the report for the president.…”
Section: Impact Of Vision 20/20mentioning
confidence: 99%